Pulmonary infection with an unusual microorganism - Mohammad Samet; Hossein Soleimani Salehabadi (Monaldi Archives for Chest Disease)
Pulmonary trichomoniasis is an underdiagnosed disease. In most cases, there is an underlying clinical condition related to immunosuppression. The results of molecular biology techniques indicate that trichomonad infections have been significantly underestimated. A 7-year-old girl with a medical history of suspected juvenile rheumatoid arthritis presented with a fever, chills, and a productive cough. Her chest computed tomography scan indicated a pericardial effusion and consolidation in the left lower lobe. In direct microscopy of the bronchoalveolar lavage fluid, we identified a motile and flagellated organism. Based on the morphology, size, and rolling motility, we identified this organism as Trichomonas hominis. The patient's fever stopped after 3 days of intravenous metronidazole administration. In immunocompromised patients with evidence of pneumonia, sputum or bronchial samples should be examined more carefully. The possibility of unusual pathogens should be considered if they do not respond to antibacterial treatments.